FEATURES OF REPRODUCTIVE MOTIVATION AND EMOTIONAL STATE OF PREGNANT WOMEN - Елена Валерьевна Литвинова; Оксана Владимировна Носкова (The Publishing House Medicine and Enlightenment, 2024)
The purpose of the work - studying the characteristics of infertility as a global medical and social problem of the world community Materials and methods. The research materials are data from state medical statistics, data from the World Health Organization, scientific and methodological publications devoted to the problem of infertility, as one of the main global problems of modern clinical reproductology and gynecology. Results. World research confirms that in 40-55 % of all cases of infertility, the causes are female partners, and men - in 20-40 %. About 30 % of infertility cases worldwide are defined as idiopathic (unexplained) and this clinical problem is defined as the absence of an obvious cause for a couple's infertility. The most common causes of female infertility are ovulation disorders (polycystic ovary syndrome), premature ovarian failure, hypothalamic dysfunction, tubal causes, endometriosis and/or uterine and cervical causes. The structure of male infertility is determined by disturbances in the normal functioning of sperm, blockages (which prevent the release of sperm), varicocele, hormonal changes, oncopathology, infections, antisperm antibodies and genetic causes caused by systemic or syndromic genetic defects. A clear definition of the molecular defect, which is caused by individual genes, makes it possible to develop and implement a targeted therapy technique for its correction. Conclusion. At the present stage of development of science and medicine, considerable experience has already been gained in the use of various methods for correcting both male and female infertility, although its prevalence levels prove the need for further search for mechanisms of therapeutic and surgical intervention in the event of the development of this problem.